2021
DOI: 10.1128/mbio.00548-21
|View full text |Cite
|
Sign up to set email alerts
|

Shared Environment and Genetics Shape the Gut Microbiome after Infant Adoption

Abstract: The composition of the human gut microbiome is highly variable, and this variation has been repeatedly tied to variation in human health. However, the sources of microbial variation remain unclear, especially early in life. It is particularly important to understand sources of early life variation in the microbiome because the state of the microbiome in childhood can influence lifelong health. Here, we compared the gut microbiomes of children adopted in infancy to those of genetically unrelated children in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Intestinal microbiota among siblings raised in different homes suggest that while the home environment acts as a “species source pool” for gut microbiota, genetic factors drive the microbial abundance once the species colonizes the gut [5]. Twins in which one twin has active IBD and the other twin is phenotypically normal exhibit similar fecal microbiota.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal microbiota among siblings raised in different homes suggest that while the home environment acts as a “species source pool” for gut microbiota, genetic factors drive the microbial abundance once the species colonizes the gut [5]. Twins in which one twin has active IBD and the other twin is phenotypically normal exhibit similar fecal microbiota.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Overall, the gut microbiota of IBD is characterized by a loss of diversity and a lower abundance of butyrate producers [2, 5-7]. Among the most prominent bacteria noted to be reduced in IBD are Faecalibacterium and Roseburia [6, 8-11].…”
Section: Faecalibacterium and Roseburiamentioning
confidence: 99%
“…According to Lee and coauthors, changes in rhizosphere soil microbiota are revealed in association with the healthy or diseased state of the rhizosphere [ 19 ]. In addition, host genetics affect human [ 20 , 21 ], animal [ 22 ] and plant microbiomes [ 23 , 24 ]. The tomato genotype influences the potential functions of soil bacterial communities.…”
Section: Soil—tomato Rhizosphere Bacteriamentioning
confidence: 99%
“…Given that the microbiota plays an important role in the inflammatory pathogenesis of CRC, the genetic–environmental contributions to the gut microbial composition is paramount to our understanding of CRC. In a recently published study, the microbiome of children who were unrelated genetically but living in a similar environment was compared to genetically related children living in different environments [ 110 ]. Using generalized dissimilarity modeling, it was found that the quantity of a specific microbial taxa was explained by host genetic similarity, whereas the species composition was dependent on environmental factors [ 110 ].…”
Section: Microbiomementioning
confidence: 99%
“…In a recently published study, the microbiome of children who were unrelated genetically but living in a similar environment was compared to genetically related children living in different environments [ 110 ]. Using generalized dissimilarity modeling, it was found that the quantity of a specific microbial taxa was explained by host genetic similarity, whereas the species composition was dependent on environmental factors [ 110 ]. This is especially important in the context of CRC, given that certain bacterial species are more likely to be associated with CRC development.…”
Section: Microbiomementioning
confidence: 99%